Adults with Attention-Deficit/Hyperactivity Disorder – A Brain Magnetic Resonance Spectroscopy Study - Dramsdahl, Margaretha; Ersland, Lars; Plessen, Kerstin J.; Haavik, Jan; Hugdahl, Kenneth; Specht, Karsten (Frontiers in Psychiatry, 2011)
Background Impaired cognitive control in individuals with Attention-Deficit/Hyperactivity Disorder (ADHD) may be related to a prefrontal cortical glutamatergic deficit. We assessed the glutamate level in the left and the right midfrontal region including the anterior cingulate cortex (ACC) in adults with ADHD and healthy controls. Methods Twenty-nine adults with ADHD and 38 healthy controls were included. We used Proton Magnetic Resonance Imaging with single-voxel point-resolved spectroscopy to measure the ratio of glutamate to creatine (Glu/Cre) in the left and the right midfrontal region in the two groups. Results The ADHD group showed a significant reduction of Glu/Cre in the left midfrontal region compared to the controls. Conclusions The reduction of Glu/Cre in the left midfrontal region in the ADHD group may reflect a glutamatergic deficit in prefrontal neuronal circuitry in adults with ADHD, resulting in problems with cognitive control.